Efek Google Meet: Sebuah Aplikasi Berbasis Pembelajaran Dalam Pembelajaran Bahasa Inggris Kala Wabah Covid-19 - Febby Pratama Putra (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
The Covid-19 outbreak has had a significant impact on our educational system. As a result of this situation, teachers have decided to switch from face-to-face to online learning. Furthermore, this circumstance resulted in low student motivation to learn English. In other words, due to monotonous learning, pupils may be too bored to participate and engage in the teaching-learning process. Some pupils were discovered to be late or unwilling to finish their homework. Google has published a number of applications as part of its Google For Education program so that instructors can use to improve their information technology (IT) oriented teaching and learning. Google Meet is one of the most popular programs that is currently available for free. This research explains how to use Google Meet as an alternate application for online learning during the outbreak, such as delivering a virtual English classroom and to make students comfortable in learning English. This paper will go through some of the theoretical and practical reasons why English teachers should be more comfortable with online learning using Google Meet. Although additional research is needed to determine the efficiency of this application in improving students' learning, it is considered that incorporating this technology into the teaching process can fundamentally revolutionize a typical classroom in many ways.